Differences between male and female growth and sexual maturation in tilapia (oreochromis mossambicus) - Bhatta, Sandip; Iwai, Toshiharu; Miura, Takeshi; Higuchi, Masato; Maugars, Gersende; Miura, Chiemi (Kathmandu University Journal of Science Engineering and Technology, 2013)
In tilapia, growth during critical periods of the life cycle varies at different ages of development and is influenced by sexual maturation. The mechanisms controlling gametogenesis and how growth affects this process are poorly understood. This study indicates that tilapia exhibit a sexually dimorphic growth pattern in which males grow faster and bigger than females. During critical periods of development growth patterns of tilapia vary between males and females as they increase in age and sexual maturation. In this study interactions between growth and reproductive development were examined by monitoring and comparing growth rates and reproductive histology. Female growth rate peaked at the very early stages of reproductive development during the cortical alveolar stages and male growth rate peaked after complete sexual maturation during spermiogenesis. The accumulation of cortical alveoli in the oocyte in females and spermiogenesis in males was determined to be the critical developmental periods of tilapia effecting growth rates. Kathmandu University Journal of Science, Engineering and Technology Vol. 8, No. II, December, 2012, 57-65